How The Role of Supplier Integration, Manager Transformational Leadership on Supply Chain Performance in Defense Industries? - Kusuma, Dony Indra; Soediantono, Dwi (AGUSPATI Research Institute, 2022)
This research is to examine the effect of supplier integration variable on supply chain performance variable i by moderating the supply chain transformational leadership style variable in the defense industry. The method used in this research is quantitative and uses a structural equation model (SEM). The respondent population of this study was 550 defense industry staff with data collection through online questionnaires and the number of samples that met the analysis criteria from 150 defense industries represented by leaders in the supply chain management section. The results of this study indicate that based on data analysis, it is concluded that the supplier integration variable has a positive effect on supply chain performance, the transformational leadership style variable has a positive effect on supply chain performance and the supplier integration variable has a positive effect on the transformational leadership style in the defense industry